2019
DOI: 10.29103/ijevs.v1i5.1714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Work Environment and Work Loads on the Performance of Police Educators in Sepolwan Lemdiklat Polri

Abstract: The objective of this causal research was to obtain information concerning: (1) the effect of work environment toward work performance; (2) the effect of workload toward work performance; and (3) the effect of work environment toward workload. The research was conducted using a survey method with a path analysis testing hypothesis. This research, principals of teachers on Police Women School - Polri has been chosen as a unit analysis and 90 samples of principals were selected at random. The results of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Based on the study results, we conclude that organizational culture affects the job satisfaction of the head of SD Negeri in Aceh Besar District. This study's results are in line with the theory proposed by Robbins and Coulter (2018: 138), which states that organizational culture directly affects one's job satisfaction (Kristiani et al, 2019;Manaf et al, 2019;Rajindra et al, 2020). If the organizational culture is high, the job satisfaction of the person will be higher (Ridlo et al, 2020;Simorangkir et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the study results, we conclude that organizational culture affects the job satisfaction of the head of SD Negeri in Aceh Besar District. This study's results are in line with the theory proposed by Robbins and Coulter (2018: 138), which states that organizational culture directly affects one's job satisfaction (Kristiani et al, 2019;Manaf et al, 2019;Rajindra et al, 2020). If the organizational culture is high, the job satisfaction of the person will be higher (Ridlo et al, 2020;Simorangkir et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…This result can be seen from the tstatistic of -2.429, which was more significant than 1.97 (t-table), and the significance value of 0.016 <0.05. This research supported previous research conducted by Desa et al (2018), Hornsby et al (2009), and Manaf et al (2019). The work environment of the Yapen Regency's local police agency was good.…”
Section: Resultssupporting
confidence: 85%
“…Work-related stress, concerning the physical work environment, is a feeling of comfort or discomfort with employees working in that location (Vischer, 2007). Previous research conducted by Desa et al (2018), Hornsby et al (2009), and Manaf et al (2019) found a significant negative relationship between work environment and work-related stress. Therefore, the third proposed hypothesis is: H3: Work environment has a negative and significant influence on police officers' work-related stress.…”
Section: Work Environmentmentioning
confidence: 72%
“…Regarding the depiction that has been clarified, the execution of the LSP undertaking of the POLRI Education and Training Institute is to keep up and guarantee the nature of the POLRI participation capability so it is as arranged, at that point it is important to do a logical investigation of the examination on the construction plan of the POLRI Institute for Education and Training Institute, the investigation of the association utilizing the idea the insightful element of hierarchical design (Robbins, 2003;Yudithia, 2019).In previous research, Manaf (2019) explained that analysis on organizational design affects the work environment on work performance; then the effect of workload on work performance; as well as the influence of the work environment on workload.…”
Section: Introductionmentioning
confidence: 99%